IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 9 TAHUN 2013 TENTANG PENGATURAN PASAR TRADISIONAL - Fajrul Umami; Zainal Hidayat (Journal of Public Policy and Management Review, 2018)
Trading is one of the chosen affairs of a decentralized system. With the existence of trade affairs, it can contribute to the economic sector of a region. One of the supporting sectors of the economy from trade affairs is the existence of traditional markets. Nowadays, the existence of traditional markets is increasingly threatened because the emerging of many modern markets. Through the Semarang City Regulation number 9 of year 2013 concerning Traditional Market Arrangements, the Local Government of Semarang City is committed to optimizing the existence of traditional markets as a part of the regional economic resources. The problem that arises is how to implement the Semarang City Regulation number 9 of years 2013 concerning Traditional Market Arrangements. The purpose of this study is to know the implementation of the Semarang City Regulation number 9 of year 2013 concerning Traditional Market Arrangements and find an influencing factors. This study uses a qualitative descriptive method, with a method of analyzing data according to Spradley and testing the validity with source triangulation techniques. The results of this study show that the Semarang City Regulation Number 9 of year 2013 concerning Traditional Market Arrangements is still not implemented well in accordance with the stated goals. Supported factors are coordination, social condition, and technology advance. Inhibiting factors are leadership, communication, commitment level of actors, and environmental conditions. Based on these concern, Dinas Perdagangan should give a leadership training program for Kepala UPTD Pasar and Kepala Pasar, repair the communication systems both vertical and horizontal, make a routine control to performance of implementing actors, and repair the facilities in traditional market with another institution.